Development of Flavor Variants and Packaging in the Fish Processing Community in Perancak Village, Jembrana District, Jembrana Regency, Bali - Singapurwa, Ni Made Ayu Suardani; Candra, I Putu; Rudianta, , I Nyoman; Armaeni, Ni Komang (Asia Pacific Network for Sustainable Agriculture, Food and Energy (SAFE-Network), 2023)
Pedetan